Antioxidant and Antimicrobial Potential of Echinacea purpurea Extract and Its Effect on Extension of Cake Shelf Life - Z Sabouri; M Barzegar; MA Sahari; H Naghdi Badi (Institue of Medicinal Plants, ACECR, 2012)
Background: Oxidation of lipids causes reduction of different properties of products that contains lipids. Nowadays, there is a growing demand for the natural antioxidants due to the harmful effects of synthetic antioxidants such as BHA, BHT and TBHQ.   Objective: In this study, extract of aerial parts of Echinacea purpurea L. was used instead of synthetic antioxidants in cake then, antioxidant and antifungal activity of Echinacea purpurea L. extract (EPE) were evaluated in cake.   Methods: The antioxidant activity of EPE and synthetic antioxidant was compared by measuring peroxide and thiobarbituric acid values during 60 days storage at 25 ºC. Antimicrobial properties of EPE were evaluated by counting of molds in Dicholoran Glycerol agar (DG18%) medium and free fatty acid analyses were assessed by IUPAC method. The effect of the extract on the color, texture, taste and total acceptability of the cake samples was carried out by a group of 20 trained panelists using Hedonic test.   Results: Different levels of EPE were able to retard the oxidation rate of cake, the 1000 ppm of it showed the lowest PV and the antioxidant activity of EPE was higher than BHA 200 ppm (p<0.01). EPE at 1500 and 2000 ppm showed the best antimicrobial activity (p<0.01). Cakes which containing the extract were well acceptable in terms of sensory parameters.  Conclusion: Results showed that EPE was more effective in controlling growing molds and lipid oxidation during 60 days storage at 25 ºC and it can be used instead of synthetic antioxidant and preservatives.